2015
DOI: 10.1038/ncb3210
|View full text |Cite
|
Sign up to set email alerts
|

Redeployment of Myc and E2f1–3 drives Rb-deficient cell cycles

Abstract: Robust mechanisms to control cell proliferation have evolved to maintain the integrity of organ architecture. Here, we investigated how two critical proliferative pathways, Myc and E2f, are integrated to control cell cycles in normal and Rb deficient cells using a murine intestinal model. We show that Myc and E2f1-3 have little impact on normal G1-S transitions. Instead, they synergistically control an S-G2 transcriptional program required for normal cell divisions and maintaining crypt-villus integrity. Surpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 69 publications
(62 reference statements)
4
57
0
Order By: Relevance
“…These observations complement and explain previous studies that implicate E2F1, E2F2, and E2F3 activity as the cause of aberrant phenotypes in Rb-knockout cells (30)(31)(32)(33). Rb regulation of activator E2Fs cannot be complemented by p107/p130, because they fail to bind with sufficient affinity.…”
supporting
confidence: 79%
“…These observations complement and explain previous studies that implicate E2F1, E2F2, and E2F3 activity as the cause of aberrant phenotypes in Rb-knockout cells (30)(31)(32)(33). Rb regulation of activator E2Fs cannot be complemented by p107/p130, because they fail to bind with sufficient affinity.…”
supporting
confidence: 79%
“…Notably, E2F1 reprogramming appears to be associated with increased Myc target gene expression, which is known to promote disease progression and poor outcome in this tumor type (79,80). These findings may also provide a molecular basis for recent observations in intestinal cancers, wherein RB pathway loss induces E2F3 and Myc cooperation (65). As such, while E2F3 does not significantly correlate with RB loss in CRPC (36), the potential for effects on the RB loss-induced E2F3 cistrome represents an intriguing node of future study.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, the increased transcriptional output for genes responsible for DNA repair suggests that putative gained functions of E2F1 upon RB depletion may drive dysregulation of genes controlling DNA damage response, even in the absence of DNA damage. Further, Myc has been shown in other tumor types to interact with E2F3 to bring about specific transcriptional programs important for cancer progression (65). Here, transcriptional data provide some of the first evidence for RB loss-driven induction of Myc targets in prostate cancer, validated in multiple model systems, suggesting that E2F1 rather than E2F3 may interact with Myc in this disease type (Supplemental Figure 6A).…”
Section: Delineation Of the Rb Loss-induced Transcriptomementioning
confidence: 72%
“…In the developing retina, we found that MYCN overexpression conferred the ability to bypass a proliferative block that otherwise limited the extent of inappropriate proliferation of Rb-deficient cells. Recently, it was shown that, upon Rb deletion, MYC can superactivate E2F transcriptional programs, in particular, G 1 /S phase-related genes (41). This role for MYC in superactivating E2F targets and driving proliferation in Rb-deleted cells may be highly relevant to the retinoblastoma that occurs with Rb deletion and MYCN amplification, as E2F target gene sets were upregulated in the Rb/TET-MYCN retinae comof 71 tumor-bearing eyes, complete elimination of retinoblastoma in the anterior chamber of the eye was eventually observed with DOX removal (average time of 21 ± 13 days) ( Figure 4F and Figure 5B).…”
Section: Discussionmentioning
confidence: 99%